Definitional analysis of concept learning environment engineering and teaching university (Pedagogy of Higher and Secondary Education, 2012)
Yakovenko T. Definitional analysis of concept learning environment engineering and teaching university.The article summarizes different approaches to the concepts of environment, educational environment, studying environment presents the author’s interpretation of them. Based on the analysis of research is formed the definition of studying environment of engineering pedagogical university.
Keywords: environment; educational environment; studying environment; engineering and teaching institution of higher education; the future engineer teacher